STALlion: a simple typed assembly language for static analysis - Nordio, Martín (2004)
Typed assembly languages have the goal of providing security guarantees, for example, for the limited use of resources in a host machine or the detection of autoupdate code. This work presents a simple typed assembly language which allows us to perform various kinds of static analysis tasks with the purpose of detecting flaws in the code security. The security policy we use guarantees type and memory safety. Moreover, wa can ensure that non-initialized variables are not read, and that there is no out-of-bound array accesses. The language we present, called STALlion, was designed in order to interpret a particular kind of imperative programs, more specifically abstract syntax tree.